2013
DOI: 10.1186/1757-7241-21-63
|View full text |Cite
|
Sign up to set email alerts
|

Equipment to prevent, diagnose, and treat hypothermia: a survey of Norwegian pre-hospital services

Abstract: IntroductionHypothermia is associated with increased morbidity and mortality in trauma patients and poses a challenge in pre-hospital treatment. The aim of this study was to identify equipment to prevent, diagnose, and treat hypothermia in Norwegian pre-hospital services.MethodIn the period of April-August 2011, we conducted a survey of 42 respondents representing a total of 543 pre-hospital units, which included all the national ground ambulance services, the fixed wing and helicopter air ambulance service, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
0
27
0
4
Order By: Relevance
“…Karlsen et al have described the equipment of different rescue services in Norway, especially the devices designed to prevent, recognize and treat accidental hypothermia, and showed that as little as 12% of ground ambulances have the opportunity to read the core temperature [15]. In Poland, Tc measurement is not possible in ground ambulances, but 28% of air rescue teams have appropriate thermometers [Darocha, unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…Karlsen et al have described the equipment of different rescue services in Norway, especially the devices designed to prevent, recognize and treat accidental hypothermia, and showed that as little as 12% of ground ambulances have the opportunity to read the core temperature [15]. In Poland, Tc measurement is not possible in ground ambulances, but 28% of air rescue teams have appropriate thermometers [Darocha, unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from hospitals in Northern Sweden in the period 2000‐2007 temperature was measured pre‐hospitally in 12.3% of cases (30/244) and the body site was recorded in 7% of these cases (rectal or epitympanic) . A survey of 42 pre‐hospital medical service providers in Norway found that air ambulances and search and rescue services were better equipped to measure body temperature than ground ambulance services . Thermometers were carried by all fixed wing air ambulance, helicopter air ambulance and search and rescue services, whereas they were present in only 12% of the ground ambulance units.…”
Section: Improving Diagnosis and Reporting Of Accidental Hypothermia mentioning
confidence: 99%
“…L'objectif de prise en charge est d'obtenir une température centrale supérieure à 34°C. Plusieurs dispositifs au-delà de la simple couverture isotherme sont utilisés par les équipes de secours en montagne pour éviter l'hypothermie comme des couvertures textiles, chauffantes, hot packs ou bubble wrap [28]. Il sera toujours utile d'installer le patient dans un hélicoptère préalablement chauffé.…”
Section: Autres Principes Thérapeutiquesunclassified